PERIAPICAL RESORPTIVE PROCESSES IN CHRONIC APICAL PERIODONTITIS: AN OVERVIEW AND DISCUSSION OF THE LITERATURE. - Angela Gusiyska (Peytchinski Publishing, 2014)
Introduction: Root resorption is a biological phenomenon, characterized by processes of cement and/or dentine depletion, resulting from the physiological or pathological activity of resorptive cells. Purpose: The aim of this article is to review of the literature on the peculiarities of the periapical resorptive processes. Conclusion: The absence of a physiological narrowing is challenging to the achievement of satisfactory early and late therapeutic results. It makes probable either the overpressing of necrotic, infected material when preparing the endodontic space or the overpressing of the sealer when sealing the root canal.